2015
DOI: 10.1007/s10552-015-0550-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic variation in IKZF1, ARID5B, and CEBPE and surrogates for early-life infections with the risk of acute lymphoblastic leukemia in Hispanic children

Abstract: Background Genome-wide association studies focusing on European-ancestry populations have identified ALL risk loci on: IKZF1, ARID5B, and CEBPE. To capture the impacts of these genes on ALL risk in the California Hispanic population, we comprehensively assessed variation within the genes and further assessed the joint effects between the genetic variation and surrogates for early life infections (presence of older siblings, daycare attendance, and ear infections). Methods Genotypic data for 323 Hispanic ALL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…‡Not represented in clinical genomic/SNP databases, but detected in one of >900 patients with myelodysplastic syndrome and reports of two individual patients with chronic thrombocytopenia 29–31§Not represented in clinical genomic/SNP databases, amino acid highly conserved, estimated allele frequency <0.1%.¶Not represented in clinical genomic/SNP databases, amino acid not highly conserved, estimated allele frequency <0.1%.**A high-resolution DNA array from peripheral blood mononuclear cells (in remission, in A.2.2) was performed as described in online supplementary table 1; the ARID5B risk allele was previously described in 21–23.††A high-resolution array from bone marrow cells at timepoint of leukaemia diagnosis pointing at secondary somatic mutations is shown in online supplementary table 1, in brief: 55,XY,+X,del(3)(p25.3p25.2),del(3)(q11.1q11.2),del(3)(q23q24),+4,del(7)(p12.2)/IKZF1,+8,+9,+10,sUPD(10)(q21.2q21.3),del(13)(q12.2),+14,del(14)(q32.12q32.13),dup(17)(q12q25.3),+18,+21,+21.‡‡Patient-reported and/or physician-documented.§§Phagocytosis and oxidative burst (dihydrorhodamine 123 flow cytometric [DHR FACS] analysis).¶¶Light microscopy, May Gruenwald-Giemsa.***ATP release, impact-R, aggregometry.†††Unbiased first interpretation of immune histochemistry.ALL, acute lymphoblastic leukaemia; ITP, immune thrombocytopenia; n.a., not applicable; n.d., not determined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…‡Not represented in clinical genomic/SNP databases, but detected in one of >900 patients with myelodysplastic syndrome and reports of two individual patients with chronic thrombocytopenia 29–31§Not represented in clinical genomic/SNP databases, amino acid highly conserved, estimated allele frequency <0.1%.¶Not represented in clinical genomic/SNP databases, amino acid not highly conserved, estimated allele frequency <0.1%.**A high-resolution DNA array from peripheral blood mononuclear cells (in remission, in A.2.2) was performed as described in online supplementary table 1; the ARID5B risk allele was previously described in 21–23.††A high-resolution array from bone marrow cells at timepoint of leukaemia diagnosis pointing at secondary somatic mutations is shown in online supplementary table 1, in brief: 55,XY,+X,del(3)(p25.3p25.2),del(3)(q11.1q11.2),del(3)(q23q24),+4,del(7)(p12.2)/IKZF1,+8,+9,+10,sUPD(10)(q21.2q21.3),del(13)(q12.2),+14,del(14)(q32.12q32.13),dup(17)(q12q25.3),+18,+21,+21.‡‡Patient-reported and/or physician-documented.§§Phagocytosis and oxidative burst (dihydrorhodamine 123 flow cytometric [DHR FACS] analysis).¶¶Light microscopy, May Gruenwald-Giemsa.***ATP release, impact-R, aggregometry.†††Unbiased first interpretation of immune histochemistry.ALL, acute lymphoblastic leukaemia; ITP, immune thrombocytopenia; n.a., not applicable; n.d., not determined.…”
Section: Resultsmentioning
confidence: 99%
“…**A high-resolution DNA array from peripheral blood mononuclear cells (in remission, in A.2.2) was performed as described in online supplementary table 1; the ARID5B risk allele was previously described in 21–23.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several genome wide and candidate gene association studies have reported strong associations between ARID5B SNPs and ALL risk in different populations. [9][10][11][12]15,[17][18][19][20][27][28][29][30] Previously, GWA studies have been conducted in populations of European, Hispanic, and African American ancestry. Our findings in Yemeni population are in agreement with these studies, confirming ARID5B SNPs as general susceptibility markers for ALL.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, abnormal expression of ARID5B pauses maturation of B-cells in the developing fetus and adds to leukemogenesis [58]. Multiple studies have suggested that IKZF1 and ARID5B SNPs are positively correlated with ALL [59][60][61][62][63][64][65][66][67][68][69][70][71], but studies showing the connection between ARID5B expression and ARID5B SNPs were missing. Ge et al (2018) demonstrated that the deletion of a single copy of IKZF1 correlates with low expression of ARID5B and that ARID5B expression is positively regulated by Ikaros [72].…”
Section: At-rich Interaction Domain 5b (Arid5b)mentioning
confidence: 99%